Modification of the CSIRO method in the long-term monitoring of slope-induced stress - Jin, Zhihao; Li, Yuan; Li, Qingwen; Liu, Zibin; Wu, Shibing; Wang, Zhuo (Frontiers in Earth Science, 2022)
The in situ stress measurement technique can be used in long-term monitoring of induced stress to obtain three-dimensional stress states in slope engineering. In the monitoring, the ambient temperature fluctuation, “zero” drift of the logging data, and stable power supply should be considered. A dual temperature compensation circuit and experimental calibration techniques are proposed to increase accuracy based on the principle of the CSIRO method and considering the effect of a long-term disturbance of temperature in slope engineering. In view of the characteristics of the stress field distribution of the slope rock, the strain gauge layout scheme for induced stress monitoring of slope rock is modified to achieve the acquisition of three parallel measurements at one measurement and a stress–strain relationship equation for multilayer elastic layers is derived. An in situ stress logging system with the function of transient logging and data-connection in power cut condition is introduced to achieve a continuous correlation of measurement data under power cut conditions. An online cloud platform is established for the slope engineering of Au Mountain Iron Mine in Maanshan City. The results show that the data deviation of logging system is ±14 με with 24 days’ power off, and errors with amount of 15% were corrected by the dual temperature compensation method. The remotely transmitted data reflect the effect of temperature changes and the evolution of strain (induced stress) in real time to satisfy the demand of long-term monitoring of slope engineering.